A Problem-Based Learning (PBL)-Based Student Worksheet Development on Green Chemistry Topics Through experimental Activities to Improve Students’ Critical Thinking Skills - Virginia, Tiara Wine (Chemistry in Education, 2025)
This study aims to develop a Problem-Based Learning (PBL)-based Student Worksheet on green chemistry topics through simple experimental activities to enhance students’ critical thinking skills. The development process employed the ADDIE model (Analyze, Design, Develop, Implement, Evaluate), involving Grade X students at SMA Negeri 12 Semarang. The worksheet centers on practical experiments involving the purification of used cooking oil and the production of aromatherapy candles, aligned with green chemistry principles. Research instruments included expert validation sheets, student response questionnaires, and multiple-choice critical thinking tests. The worksheet achieved average validity scores of 99% from media experts and 90% from material experts, both of which are categorized as highly valid. Its effectiveness was evaluated through pretest and posttest assessments, revealing an increase in students’ mean scores from 70.98 to 86.26, with a normalized gain (N-Gain) of 0.58, classified as moderate to high. Furthermore, 84.40% of students demonstrated high to very high levels of critical thinking skills. Student responses toward the worksheet were highly positive, with an average rating of 97%. These results indicate that the PBL-based worksheet on green chemistry is valid, effective, and significantly supports the learning process and outcomes while fostering critical thinking, environmental awareness, and sustainability.